Vejrforholdene i landbrugsåret 1950—51.(Fra 1. oktober 1950—30. september 1951). - Krogsriis, C. A. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i landbrugsåret 1950—51.(Fra 1. oktober 1950—30. september 1951).